Pengaruh Brand Equity, Brand Trust, Dan Brand Experience Terhadap Loyalitas Pelanggan ( Studi Pada Pelanggan Juragan Es di Kab Semarang ) - Abdullah Abdullah (CV. ALIM'SPUBLISHING, 2026)
Abstract. Competition conditions in the business world are currently increasingly tight, one of the products that must remain viable is ice tea products.. This research aims to find out how much influence Brand Equity, Brand Trust and Brand Experience have on customer loyalty for Juragan ice in the city of Semarang. The sampling method uses the Probability Sampling Technique with a purposive sampling method using the Slovin formula calculation. The population in this research is Juragan ice users in the city of Semarang, with a sample of 100 respondents and with Likert scale measurements. The analysis in this research was processed using SPSS software.The results of the research can be concluded that Brand Equity has an influence on customer loyalty for Juragan ice products with a significance value of 0.000 < 0.05 and t count 20.433 > t table 1.966, Brand Trust has an influence on customer loyalty for Juragan ice products with a value of 0.000 < 0, 05 and t count 3.663 > t table 1.966, and Brand Experience has an influence on customer loyalty for Juragan ice products with a significant value of 0.000 < 0.05 and t count 14.424 > t table 1.966. The research results also show that the results of the model feasibility test (f test) have a significance value of 0.000 <0.05. So it can be concluded that this test is feasible. This shows that the Juragan ice brand is trusted by the public because its quality is good.